Active Degassing of Deeply Sourced Fluids in Central Europe: New Evidences From a Geochemical Study in Serbia. (13th November 2021) - Randazzo, P.; Caracausi, A.; Aiuppa, A.; Cardellini, C.; Chiodini, G.; D'Alessandro, W.; Li Vigni, L.; Papic, P.; Marinkovic, G.; Ionescu, A.
Abstract: We report on the results of an extensive geochemical survey of fluids released in the Vardar zone (central‐western Serbia), a mega‐suture zone at the boundary between Eurasia and Africa plates. Thirty‐one bubbling gas samples are investigated for their chemical and isotopic compositions (He, C, Ar) and cluster into three distinct groups (CO2 ‐dominated, N2 ‐dominated, and CH4 ‐dominated) based on the dominant gas species. The measured He isotope ratios range from 0.08 to 1.19 Ra (where Ra is the atmospheric ratio), and reveal for the first time the presence of a minor (<20%) but detectable regional mantle‐derived component in Serbia. δ 13 C values range from −20.2‰ to −0.1‰ (versus PDB), with the more negative compositions observed in N2 ‐dominated samples. The carbon‐helium relationship indicates that these negative δ 13 C compositions could be due to isotopic fractionation processes during CO2 dissolution into groundwater. In contrast, CO2 ‐rich samples reflect mixing between crustal and mantle‐derived CO2 . Our estimated mantle‐derived He flux (9.0 × 10 9 atoms m −2 s −1 ) is up to 2 orders of magnitude higher than the typical fluxes in stable continental areas, suggesting a structural/tectonic setting favoring the migration of deep‐mantle fluids through the crust. Key Points: Chemical and isotopic composition of natural gas manifestations along the Serbian Vardar zone are controlled by mixing processes and fraction during water‐gas‐rock interactions in shallow crustal layers Mantle‐derived He flux of 2 orders of magnitude higher than normally found in stable continental areas are estimated Mantle volatiles and heat are sourced directly from the mantle supporting the asthenosphere up‐rise and delamination processes at the mantle‐crust boundary recognized in the studied area